Characterization of skin reactions and pain reported by patients receiving radiation therapy for cancer at different sites - Gewandter, Jennifer S. (J Support Oncol, 2013)
BACKGROUND: Skin reactions and pain are commonly reported side effects of radiation therapy (RT). OBJECTIVE: To characterize RT-induced symptoms according to treatment site subgroups and identify skin symptoms that correlate with pain. METHODS: A self-report survey, adapted from the MD Anderson Symptom Inventory and the McGill Pain Questionnaire, assessed RT-induced skin problems, pain, and specific skin symptoms. Wilcoxon Sign Ranked tests compared mean severity of pre- and post-RT pain and skin problems within each RT-site subgroup. Multiple linear regression (MLR) investigated associations between skin symptoms and pain. RESULTS: Survey respondents (n=106) were 58% female and on average 64 years old. RT sites included lung, breast, lower abdomen, head/neck/brain, and upper abdomen. Only patients receiving breast RT reported significant increases in treatment site pain and skin problems (p≤0.007). Patients receiving head/neck/brain RT reported increased skin problems (p<0.0009). MLR showed that post-RT skin tenderness and tightness were most strongly associated with post-RT pain (p=0.066 and p=0.122, respectively). LIMITATIONS: Small sample size, exploratory analyses, and non-validated measure. CONCLUSIONS: Only patients receiving breast RT reported significant increases in pain and skin problems at the RT site, while patients receiving head/neck/brain RT had increased skin problems, but not pain. These findings suggest that the severity of skin problems is not the only factor that contributes to pain, and interventions should be tailored to specifically target pain at the RT site, possibly by targeting tenderness and tightness. These findings should be confirmed in a larger sampling of RT patients.